This preview shows page 1. Sign up to view the full content.
Unformatted text preview: we will get a single value from the multiplication. Likewise, we will only get a
single value if we add 1 onto a number. Therefore, it seems plausible that based on the operations
involved with plugging x into the equation that we will only get a single value of y out of the
So, this equation is a function.
[Return to Problems] (b) y = x 2 + 1
Again, let’s plug in a couple of values of x and solve for y to see what happens. x = -1: y = ( -1) + 1 = 1 + 1 = 2 x = 3: y = ( 3) + 1 = 9 + 1 = 10 2 2 Now, let’s think a little bit about what we were doing with the evaluations. First we squared the
value of x that we plugged in. When we square a number there will only be one possible value.
We then add 1 onto this, but again, this will yield a single value.
So, it seems like this equation is also a function.
Note that it is okay to get the same y value for different x’s. For example, x = -3 : y = ( -3) + 1 = 9 + 1 = 10
2 We just can’t get more than one y out of the equation after we plug in the x.
[Return to Problems] (c) y 2 = x + 1
As we’ve done with the previous two equations let’s plug in a couple of value of x, solve for y
View Full Document
This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.
- Spring '12